Exchange Rate Appreciation As a Signal of a New Policy Stance - Winckler, Georg (IMF Working Papers; Working Paper, 1991)
It is shown in a game theoretic framework that it may pay off to signal a 'conservative' policy stance--giving a high priority to price stability--by appreciating the exchange rate. Such an appreciation demonstrates to domestic producers and more precisely to the trade union that the new policy stance is meant to be serious. An example explores the welfare implication for the policy maker and the trade union. The empirical background of the paper refers to the monetary policy in Europe. It explains the occurrence of exchange rate commitments to the deutsche mark, with appreciated rates.